Green Finance and Financial Innovation on Business Sustainability: The Role of Green Innovation - Kusuma, Desta Rizky; Hidayat, Taufik; Anggraini, Sinta Putri (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2025)
This study examines the influence of green finance and financial innovation on business sustainability, with green innovation positioned as a mediating factor in the banking sector of Yogyakarta. The paper advances innovation studies by demonstrating the asymmetric role of green finance and financial innovation in driving sustainability, highlighting how innovation in finance—not merely funding—becomes a decisive lever for sustainable outcomes. Employing a quantitative approach with path analysis, data from 352 respondents were analyzed using Smart PLS 4.0. Findings reveal that while green finance significantly affects business sustainability, it fails to directly stimulate green innovation. In contrast, financial innovation significantly drives both green innovation and sustainability, with partial mediation evident. These insights challenge conventional assumptions that financing alone catalyzes green innovation, underscoring the need for deeper institutional creativity in financial practices. For managers, the study stresses aligning financial innovation with sustainability strategies to accelerate sustainable development goals.